Application of Restorative Justice Against Narcotics User Teenagers Types of Drugs: Penerapan Restorative Justice Terhadap Remaja Pengguna Narkotika Jenis Obat-Obatan - Erwinsyah Bangun, Fikri (UPMI Proceeding Series, 2023)
The regulation regarding narcotics according to Law Number 35 of 2009 concerning narcotics regulates efforts to eradicate narcotics crimes through threats of fines, imprisonment, and life imprisonment and death penalty and for this it stipulates criminal sanctions for the abuse of narcotics caught in articles 54 and 127 against abuse of illegal drugs based on Law Number 35 of 2009 concerning Narcotics. So that one of the considerations that must be upheld by the authorities, especially the government and legislative institutions that make laws as a deterrent effect, frightening effect, relative effect, but also aims to protect the future of a nation. Restorative Justice is an approach model that appears in efforts to resolve criminal cases. In contrast to the approach used in the conventional justice system which focuses more on the deterrent effect for the perpetrators of crime (woman offender), this approach focuses more on the direct participation of perpetrators, victims and also the community in the process of settling criminal cases.At present, restorative justice is really needed in solving various types of crimes, especially certain crimes which if handled retributively do not provide significant benefits, but instead cause new losses for both victims and the state, including in this case, namely narcotics crimes in particular. non-dealer users.